2024
DOI: 10.1039/d3se01393f
|View full text |Cite
|
Sign up to set email alerts
|

An efficient Ni3S2–Ni electrode constructed by a one-step powder metallurgy approach for the hydrogen evolution reaction

Yang Zhao,
Xiaoqian Shi,
Bin Zhang
et al.

Abstract: A one-step powder metallurgy process using Ni and nano S powder was proposed to prepare a Ni3S2–Ni electrode. Numerous Ni3S2 nano protuberances on the surface and strong bonding between inter-connected Ni networks significantly improve the catalytic performance and durability of the HER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…1–3 Clean energy resources are high-profile research topics of the century, and hydrogen energy has been identified as a clean and sustainable resource. 4,5 Hydrogen may be a significant and extraordinary energy resource for modern technology. 6 Among the several techniques used for the production of hydrogen, electrochemical water splitting is considered the most efficient and reliable approach.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Clean energy resources are high-profile research topics of the century, and hydrogen energy has been identified as a clean and sustainable resource. 4,5 Hydrogen may be a significant and extraordinary energy resource for modern technology. 6 Among the several techniques used for the production of hydrogen, electrochemical water splitting is considered the most efficient and reliable approach.…”
Section: Introductionmentioning
confidence: 99%